Advances in Sensors and Sensing for Technical Condition Assessment and NDT - Boczar, Tomasz; Kunicki, Michał; Wotzka, Daria; Nagi, Łukasz; Kozioł, Michał (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The adequate assessment of key apparatus conditions is a hot topic in all branches of industry. Various online and offline diagnostic methods are widely applied to provide early detections of any abnormality in exploitation. Furthermore, different sensors may also be applied to capture selected physical quantities that may be used to indicate the type of potential fault. The essential steps of the signal analysis regarding the technical condition assessment process may be listed as: signal measurement (using relevant sensors), processing, modelling, and classification. In the Special Issue entitled "Advances in Sensors and Sensing for Technical Condition Assessment and NDT", we present the latest research in various areas of technology.